Thymic hyperplasia as a rare etiology of pure red cell aplasia - Arsenović, Isidora; Leković, Danijela; Šefer, Dijana; Ivanović, Jelena; Smiljanić, Mihajlo; Bogdanović, Andrija (Vojnosanitetski pregled, 2024)
Introduction. Thymic hyperplasia is a rare condition caused by an increase in cellular thymic mass and, in some cases, is associated with autoimmune diseases, such as pure red cell aplasia (PRCA). Thymectomy is considered the most effective therapy for PRCA associated with thymoma, with a 31.5% complete remission rate. Other treatments may induce partial remissions, but complete remission remains elusive. A case of PRCA attributed to thymic hyperplasia is presented, highlighting the effectiveness of thymectomy. Case report. A previously healthy 18-year-old woman presented with severe anemia and after hematological evaluation, including bone marrow biopsy confirmation, a diagnosis of PRCA was made. Immunological and virological analyses were unremarkable. Given the history of thymoma in the family and the known association between thymoma and PRCA, a chest magnetic resonance imaging was performed, which proved the existence of thymic hyperplasia. The patient underwent the least invasive surgical procedure – total thymectomy using video-assisted thoracic surgery approach. Pathohistological examination of the operative material confirmed the presence of thymic hyperplasia with a simple intrathymic cyst. Following thymectomy, the patient’s hematological values significantly improved. Conclusion. The course and outcome of the patient’s treatment support the role of thymectomy in PRCA associated with thymic hyperplasia. However, further research and follow-up are needed to optimize management strategies for this rare condition.
Keywords: anemia; diagnosis; histological techniques; red-cell aplasia, pure; thoracic surgery, video-assisted; thymoma; thymus hyperplasia